EFFICIENCY OF RAW MATERIAL USING THE ECONOMIC ORDER QUANTITY METHOD - Cahyani, Gita; Slamet, Achmad (Universitas Negeri Semarang, 2019)
Optimal supply of raw materials is an important factor in the fluency of the production process in a company. Reviews These raw materials can be controlled by using eertain methods, one of that is a Economic Order Quantity (EOQ) method roomates has a better level of calculation accuracy than conventional methods. This study is quantitative research, the which has a goal to examine more deeply about the use of methods quantiy Economic Order (EOQ) in the cantrol af raw materials companies Brownies Burn Lyn's. The result Showed the optimal inventory of raw materials flour using EOQ method is 2445kg with a frequency of purchase as 5 times, safety stock is 248kg and ROP done at the time the raw material warehouse at 338kg and TIC Rp 2.945.963.00 optimal supplies of sugar with EOG method is 2998 kg, with a frequency of purchive as 6 uimes safety stock is 330 kg and ROP should be done at the time the raw 450kg while the TKR Rp3,46l 934,00.The quantity of supplies raw material warehouse material with EOG method is more efficient than the company conventional method inventary optimal inventory and total cost savings can be Obtained by the method of EOO so the company can gain the maximum profit. For the furture Similar themes of research on the subject of using optimal inventory in micro and medium enterprises is expected to compare with methods of optimal order invetory in order to Obtain more effective and efficient result.